2017
DOI: 10.1186/s12957-017-1273-6
|View full text |Cite
|
Sign up to set email alerts
|

Oncological outcome of complete response after neoadjuvant chemotherapy for breast conserving surgery: a systematic review and meta-analysis

Abstract: BackgroundWith limited sample sizes and single-institution designs, how complete response (CR) after neoadjuvant chemotherapy (NAC) influences breast conserving surgery (BCS) and its value in prognosis are not clear.MethodsA systematic research review was conducted using electronic database. The rate of clinical complete response (cCR) in BCS after NAC and these pathological CR (PCR) and non-pCR BCS patients’ local recurrence-free survival (LRFS), distance recurrence-free survival (DRFS), overall survival (OS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…Triple negative breast cancer and lack of pathological response were associated with higher locoregional recurrence risk. Li et al [ 16 ] reported the results of meta-analysis that patients who achieved a pCR after NAC had significantly lower rates of local and distant RFS.…”
Section: Discussionmentioning
confidence: 99%
“…Triple negative breast cancer and lack of pathological response were associated with higher locoregional recurrence risk. Li et al [ 16 ] reported the results of meta-analysis that patients who achieved a pCR after NAC had significantly lower rates of local and distant RFS.…”
Section: Discussionmentioning
confidence: 99%
“…All enrolled cases were diagnosed and confirmed by core needle biopsy prior to NACT. Before NACT, 8 were triple-negative subtype, respectively. There was no significant association between tumor molecular subtypes and SIRI (Table 4).…”
Section: Correlation Between Siri and Breast Cancer Molecular Subtypesmentioning
confidence: 99%
“…[5][6][7] Neoadjuvant chemotherapy (NACT) is the gold standard of care for locally advanced cancer and has been widely used to the treatment for locally advanced breast cancer. 8 According to the NACT for breast cancer, the breast-conserving surgery rate is increasing, and the tumor stage is decreasing. 9 Many NACT regimens have been applied to the treatment for breast cancer; however, there are no internationally generally accepted NACT regimens for patients with advanced breast carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Neoadjuvant chemotherapy (NACT) is the standard of care for breast cancer with aggressive biological features ( Li et al, 2017 ). NACT can improve the resectability of locally advanced breast cancer and inflammatory breast cancer, decrease the pathology stage and improve the feasibility and cosmetic effect of breast-conserving surgery, and decrease morbidity and the extent of axillary surgery in women with significant nodal disease ( Echeverria et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%